Islam dan negara dalam politik orde baru (1966-1994) = Islam and State in The New Order Politics (1966-1994) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The relationship of Islam and the State in a country where majority of the people are Moslem is frequently marked by uneasy feeling. In Indonesia, such phenomena is also encountered. It is this topic which this study focuses on, restricting to the era of New Order (1966-1994). The study has the objective of elucidating the changes which had taken place in the relationship of Islam and the State during the era of New Order (1966-1994) from antagonistic (1967-1981) to reciprocally critical (19824985) and finally accomodative (1985-1994). The relationship of Islam and the State was analyzed based on perspective theory of State and Civil Society. Structural approach was used. The study was descriptive and evaluative. Aggregat data and docu- mentary data were collected through literature study.Hence, analytical method was adopted in this study was qualitative. The results revealed that: First, the relationship of Islam and the State during the era of New Order was influenced by suppressor variable is New Order political model and Islamic general features of the Indonesian. Secondly, from that very fact, the accomodative relationship of Islam and the State is bidirectional. In one way the State accomociates the needs of Islam. In another way Islam provides supports to the State. Thirdly, the changes in relationship Islam and the Sfate coincides with the change of State perception to becoming positive to Islam, and vice versa. Fourthly, the State perception to Islam was changed since (1) Trauma of Islamic rebellion in the past has faded. (2) There was a better understanding, appreciation, and-perception among member of elite society in the State itself towards Islamic society. It is due to involvement of figures known to have strong background of Islam in the government, a phenomenon known as "Santrisasi Priya.", and due tobetter understanding andperception from the elite society in the government towards Islam, particularly from the president himself, a phenomenon known as "Santrisasi Priyayi"